2017
DOI: 10.1021/acs.estlett.6b00471
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidation of Iodide (I) and Hypoiodous Acid (HOI) by Peroxymonosulfate (PMS) and Formation of Iodinated Products in the PMS/I/NOM System

Abstract: In this work, the kinetics of transformation of iodide (I–) and hypoiodous acid (HOI) by peroxymonosulfate (PMS) and potential formation of worrisome iodinated products in the presence of natural organic matter (NOM) were investigated. As the pH increased from 5 to 10, the apparent second-order rate constants of reaction of PMS with I– gradually decreased from 1.01 × 103 to 3.86 × 102 M–1 s–1, while those for HOI increased dramatically from 1.08 × 102 to 7.90 × 104 M–1 s–1. The obtained pH-dependent rate profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 56 publications
(80 reference statements)
2
34
0
1
Order By: Relevance
“…Previous studies have postulated that reaction of I − with either the MPO/H 2 O 2 /Cl − system, or its product HOCl, forms HOI and hence IO 3 − via a rapid disproportionation reaction that regenerates a proportion of the I − originally consumed (Equation (2)) [64]. These secondary products, such as IO 3 − , would be expected to be less reactive than HOI itself [65]. The formation of IO 3 − on reaction of HOCl with I − was confirmed by spectrophotometric assay after reaction of HOCl (100 μM) with equimolar concentrations of I − at 21 °C over a period of 20 min (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have postulated that reaction of I − with either the MPO/H 2 O 2 /Cl − system, or its product HOCl, forms HOI and hence IO 3 − via a rapid disproportionation reaction that regenerates a proportion of the I − originally consumed (Equation (2)) [64]. These secondary products, such as IO 3 − , would be expected to be less reactive than HOI itself [65]. The formation of IO 3 − on reaction of HOCl with I − was confirmed by spectrophotometric assay after reaction of HOCl (100 μM) with equimolar concentrations of I − at 21 °C over a period of 20 min (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Im et al [39] identified 4-hydroxycumyl alcohol (HCA), a product of oxidation of BPA electrons by MnO 2 which undergoes microbiological degradation faster than bisphenol itself. Bisphenol transformation in soil is greatly affected by iodide ion (I − ), which is oxidised to hypoiodic acid (HOI) or molecular iodine (I2) [40]. Vikesland et al [41] demonstrated that I − stimulates transformations of bisphenols, triclosan and phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Asam hypoiodous merupakan senyawa yang terbentuk dari reaksi kombinasi antara hidrogen peroksida H 2 O 2 dan KIO 3 yang dikatalisis oleh enzim peroksidase (Al-Baarri et al, 2018). Senyawa ini tergolong dalam kelompok asam lemah yang tersusun atas ion H + dan OI - (Li et al, 2017). Kedua ion tersebut dapat berikatan dengan struktur luar dari fenol tanaman yang bersifat hidrofilik yang bertanggungjawab dalam melakukan aksi antioksidan (Gulcin et al, 2010).…”
Section: Hasil Dan Pembahasan Aktivitas Antioksidanunclassified